2005
DOI: 10.1007/s00106-004-1146-5
|View full text |Cite
|
Sign up to set email alerts
|

Magnetisches Drug Targeting—ein neuer Ansatz in der lokoregionären Tumortherapie mit Chemotherapeutika

Abstract: Magnetic Drug Targeting offers an unique opportunity to treat tumors locoregionally with chemotherapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 11 publications
(2 reference statements)
5
18
0
1
Order By: Relevance
“…[8][9][10] Nevertheless, some of the data on MCM-41 cell-based screens were found to be misleading due to the interference of MCM-41 itself with the 2,5-diphenyltetrazolium salt (MTT) used to asses toxicity. 11,12 Iron oxide NPs (Fe 2 O 3 or Fe 3 O 4 ) have been widely applied as magnetic drug targeting systems 13,14 and contrast agents in magnetic imaging. Cell-based cytotoxicity studies have shown that human mesothelioma cells are sensitive to Fe 2 O 3 -NPs exposure, but rodent 3T3 cells are non-responsive.…”
Section: 7mentioning
confidence: 99%
“…[8][9][10] Nevertheless, some of the data on MCM-41 cell-based screens were found to be misleading due to the interference of MCM-41 itself with the 2,5-diphenyltetrazolium salt (MTT) used to asses toxicity. 11,12 Iron oxide NPs (Fe 2 O 3 or Fe 3 O 4 ) have been widely applied as magnetic drug targeting systems 13,14 and contrast agents in magnetic imaging. Cell-based cytotoxicity studies have shown that human mesothelioma cells are sensitive to Fe 2 O 3 -NPs exposure, but rodent 3T3 cells are non-responsive.…”
Section: 7mentioning
confidence: 99%
“…The most striking examples have been presented in Alexiou et al (2005) in experiments with rabbits with artifically initiated limb tumours. It is demonstrated that treatments using only 20% of the standard drug amount with an active magnetic targeting showed full recovery of treated limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, one study of nanoparticles loaded with a chemotherapeutic agent has shown reversal of multidrug resistance. 6 At present, Fe 3 O 4 is one of the most commonly used nanoparticle materials, with low toxicity, magnetic properties, and minimal impact on body metabolism. 6,26,29 In order to make the magnetic nanoparticles accumulate locally at the tumor site, an external alternating magnetic field is usually required, as well as magnetic nanoparticles with additional hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…6 At present, Fe 3 O 4 is one of the most commonly used nanoparticle materials, with low toxicity, magnetic properties, and minimal impact on body metabolism. 6,26,29 In order to make the magnetic nanoparticles accumulate locally at the tumor site, an external alternating magnetic field is usually required, as well as magnetic nanoparticles with additional hyperthermia. 29 Hyperthermia is an old but nowadays rapidly developing method of treating cancer, whereby a temperature of 40°C-45°C is considered optimal for hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation